A pilot controlled trial of a combination of electroacupuncture and psychological intervention for post-stroke depression - Huanyuan Wang; Yan Li (Elsevier, 2022)
Objective: This study was to investigate effects of a combination of electroacupuncture (EA) and psychological intervention (PI) for post-stroke depression (PSD) and provide treatment suggestions Methods: In a single-blind, randomized controlled trial, 49 patients with PSD were randomly divided into two groups, PI group (n = 23) and PI+EA group (n = 26). PI group received PI 2 times a week by a professional psychologist. In addition to PI treatment, PI+EA group was treated with EA at GB13 and HT7, 30 min, 5 times a week, 4 weeks as a course of treatment, a total of 12 weeks. The 17-item Hamilton Rating Scale for Depression (HAMD-17) and Lo Knapp Ron J's sleep score table were measured before treatment, 4 weeks, 8 weeks and 12 weeks after treatment. Results: After 12 weeks of PI or PI+EA therapy, 42 of 49 patients were effective and 7 were ineffective, with an effective rate of 85.7 %. Among them, the effective rate of PI group alone was 78.3 %, and the effective rate of PI+EA group was 92.3 %. Compared with values of PI, HAMD-17 values at 8 weeks of PI+EA treatment were significantly decreased (P < 0.01). At the same time, Sleep Score table was significantly decreased after PI+EA treatment (P < 0.05). Incidence of adverse events was not different in the two groups Conclusion: A combination of EA and PI maybe an effective and safe treatment option for PSD, which is statistically more significant than PI treatment alone. Due to small samples involved in this pilot study, further research is needed to see whether a combination of EA and PI will match the results of this pilot study.